Penerapan Kebijakan Pencegahan Korupsi dalam Lembaga - Jordan Ang Saputra (Majelis: Jurnal Hukum Indonesia, 2024)
Corruption is one of the biggest challenges for many companies in various industries. Implementing an anti-corruption policy is an important step in maintaining integrity, reputation and continuity of the institution. This article explains how companies can design and implement effective anti-corruption policies. Key elements of this policy include employee training, internal audits, transparency of business processes, and the application of strict sanctions for violations. Furthermore, a culture of integrity in the work environment must be built through good examples from top management. Technology can also facilitate monitoring and oversight and reduce the risk of corruption. With strict guidelines and the support of all stakeholders within the company, anti-corruption efforts can be implemented more effectively and help companies achieve sustainable growth.